2016
DOI: 10.1038/srep37322
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysteroid-containing food supplements from Cyanotis arachnoidea on the European market: evidence for spinach product counterfeiting

Abstract: Phytoecdysteroids like 20-hydroxyecdysone (“ecdysterone”) can exert a mild, non-hormonal anabolic/adaptogenic activity in mammals, and as such, are frequently used in food supplements. Spinach is well-known for its relatively low ecdysteroid content. Cyanotis arachnoidea, a plant native in China, is among the richest sources of phytoecdysteroids, and extracts of this plant are marketed in tons per year amounts via the internet at highly competitive prices. Here we report the investigation of a series of food s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 12 publications
0
41
0
6
Order By: Relevance
“…In Helicoverpa armigera, 20E causes a switch from autophagy to apoptosis (11), counteracts the action of insulin (12), promotes phosphatidylinositol-3,4,5-trisphosphate 3-phosphatase (PTEN) expression (13), and promotes the Hippo pathway to induce apoptosis (14). Furthermore, 20E is used as a food additive to maintain the glucose-lipid balance in humans, without the side effects of mammalian hormones (15).…”
mentioning
confidence: 99%
“…In Helicoverpa armigera, 20E causes a switch from autophagy to apoptosis (11), counteracts the action of insulin (12), promotes phosphatidylinositol-3,4,5-trisphosphate 3-phosphatase (PTEN) expression (13), and promotes the Hippo pathway to induce apoptosis (14). Furthermore, 20E is used as a food additive to maintain the glucose-lipid balance in humans, without the side effects of mammalian hormones (15).…”
mentioning
confidence: 99%
“…They also discovered other structurally related polyhydroxylated sterols, such as brassinosterol phytohormones (Kripach et al, 2000). In addition to ferns (Jizba et al, 1967) and vascular plants (Dinan & Lafont, 2006;Kumpun et al, 2011;Lafont et al, 2011;Hunyadi et al, 2016), vitamin D 1 was found in mushrooms (Vokáč et al, 1998), crustaceans (Horn et al, 1968, marine arthropods (Pycnogonids) (Tomaschko & Bückman, 1992), insects (Karlson, 1966;Sláma et al, 1974Sláma et al, , 1993, Japanese quails (Koudela et al, 1995;Sláma et al, 1996), mice (Stopka et al, 1999, Smagghe, 2009, domestic animals (Syrov, 1984;Sláma & Lafont, 1995;Košár et al, 1997;Krátký et al, 1997;Dittrich et al, 2000;Kholodova, 2001;Dinan & Lafont, 2006;Jadhav et al, 2007) and humans (Koolman & Moeller, 1986;Bhaswaid et al, 1991;Gharib et al, 1991;Sláma & Lafont, 1995;Kholodova et al, 2001). Sláma (1979) was the fi rst to propose that vitamin D 1 could be a reserve material for growth of tissues in plants.…”
Section: Distribution and Sources Of Vitamin Dmentioning
confidence: 99%
“…In addition to plants containing relatively substantial amounts of vitamin D 1 , like for example, the fern Polypodium vulgare L. the daisies Leuzea carthamoides (Willd.) and Serratula coronata L. as well as the mint, Ajuga turkestanica (Jizba et al, 1967;Volodin, 2003;Jadhav et al, 2007;Dinan et al, 2009;Lafont et al, 2011), vitamin D 1 is a common constituent of vegetable foods like, Quinoa (Chenopodium quinoa; 0.03%; Kumpun et al, 2011); spinach (Spinacia oleracea L., 0.01%; Hunyadi et al, 2016) and Suma root (Hebanthe eriantha, 0.66%; Hunyadi et al, 2016). A more recent preparation, SERPISTEN, registered in Russia, uses the purifi ed extracts of vitamin D 1 from Serratula coronata L. (Volodin, 2003;Ufi mtsev et al, 2009).…”
Section: Th E Neglected Role Of Vitamin D 1 In Human Health Carementioning
confidence: 99%
“…These ecdysteroid-containing products are marketed all around the world with the purpose of muscular development or for the promise of other health benefits [37,38]. Description of numerous beneficial effects of 20E supplementation can be found on the internet, though it is hard to evaluate the reliability of these statements, since most of them have no human studies behind.…”
Section: Biological Activity and Potential Application Of Ecdysteroidsmentioning
confidence: 99%
“…Preparations made from Leuzea carthamoides -a plant containing high levels of ecdysteroids, especially 20E -were observed to have such an effect. For example a green tea, called 'maralan' is made from this plant and consumed extensively in Central Europe to improve general wellbeing, increase appetite and improve digestion [13,38]. 20E was also shown to exert some immunomodulatory effects in mice, rats and humans [40,41,42].…”
Section: Biological Activity and Potential Application Of Ecdysteroidsmentioning
confidence: 99%